The Art of the Essay NO. 4. - Weinberger, Eliot (Paris Review)
An interview with Eliot Weinberger, a writer and essayist is presented. He discussed his approach to the impersonal essay, explaining that his works draw on scholarly articles, and global sources to create literary essays that often resemble encyclopedia entries. He mentioned that while he is widely recognized for his translations of writers like Octavio Paz, and Bei Dao, he has never considered himself primarily a translator, emphasizing that his main focus has always been writing essays.